Perancangan Pusat Jajanan dan Wisata Kuliner Olahan Sagu Di Selatpanjang Dengan Pendekatan Arsitektur Bioklimatik - Dede Mefriadi; Wahyu Hidayat; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Geographically, Selatpanjang is located on the eastern coast of the island of Sumatra which is bordered by a number of neighboring countries, namely Singapore and Malaysia, with the territory being an archipelago. Selatpanjang is very famous for its processed dishes made from sago, otherwise known as sago flour. Sago flour is processed product obtained from processing terraces of sago palm or sago trees. Sago flour has physical characteristics similar to tapioca flour. Sago can also be used as a staple substitute for rice which contains lots of carbohydrates. The demand for providing culinary facilities and processed sago snacks cannot be separated from the natural resources produced from Selatpanjang itself, namely sago, so the need to provide facilities to raise the potential of natural resources in Selatpanjang, namely in the form of the Snack Center and Processed Sago Culinary Tour facilities. The main factor that drives the establishment of a culinary facility for processed sago, is the lack of interest from the public to consume the processed sago, even though the potential natural resources produced from the Meranti Islands are mostly sago or sago starch. In addition, to encourage tourism activities in Selatpanjang in the form of culinary tours. The design of the Sago Processed Snack and Culinary Center in Selatpanjang uses a bioclimatic architecture approach which is known to be very friendly to the surrounding environment, and also to optimize the use of energy used in buildings, such as lighting, ventilation and other energy use in order to achieve comfort for its users. Keyword : Friendly, culinary, potency, Sago